2018
DOI: 10.18535/jmscr/v6i5.117
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Imbalance in Patients of Acute Myocardial Infarction: A Study from Central India

Abstract: Background: Acute myocardial infarction is one the manifestations of coronary heart disease, leading to morbidity and mortality. Electrolytes such as sodium and potassium are considered to be major determinants of electrophysiological properties of myocardial membrane and their imbalance after an episode of AMI is common. Hence, the present study was planned with the aim to evaluate serum sodium and potassium in patients of AMI. Materials and Methods: The present study included 50 patients of AMI and 50 normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…2,34 Electrolyte imbalance is often associated with high mortality among hospitalized patients with AMI. 9,35 There is a lack of data about such issues in Palestine, especially among patients with AMI. One study conducted in 2012 to assess the relationship of serum potassium levels found that hyper-or hypokalemia is asso-ciated with mortality among patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,34 Electrolyte imbalance is often associated with high mortality among hospitalized patients with AMI. 9,35 There is a lack of data about such issues in Palestine, especially among patients with AMI. One study conducted in 2012 to assess the relationship of serum potassium levels found that hyper-or hypokalemia is asso-ciated with mortality among patients with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…These imbalances are connected to many interrelated factors such as vasopressin, the renin-angiotensin-aldosterone system, and catecholamine stimulation 2,34. Electrolyte imbalance is often associated with high mortality among hospitalized patients with AMI 9,35…”
Section: Discussionmentioning
confidence: 99%
“…Electrolyte imbalances are common in STEMI subjects ( 31 , 32 ), and heart rhythm is influenced by electrolyte concentration ( 33 ). Although hyperkalemic STEMI is rare ( 34 ), our study revealed that 28.1% of STEMI subjects with hyperkalemia had RWMA in the LAD territory.…”
Section: Discussionmentioning
confidence: 99%